2008
DOI: 10.1111/j.1479-828x.2008.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparative study on sublingual versus vaginal administration of misoprostol for termination of pregnancy between 13 to 20 weeks

Abstract: Both sublingual and vaginal administrations of misoprostol are equally effective in inducing medical abortion during second trimester but sublingual route was preferred by the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 18 publications
4
25
2
2
Order By: Relevance
“…Drug related side effects and procedure related complications were very low, which is comparable to different studies. 9,13,15 In present prospective study 98% women aborted within 16 hours, which is comparable to about ninety percent as reported by other studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Drug related side effects and procedure related complications were very low, which is comparable to different studies. 9,13,15 In present prospective study 98% women aborted within 16 hours, which is comparable to about ninety percent as reported by other studies.…”
Section: Discussionsupporting
confidence: 77%
“…Mean induction abortion interval in our study was 12.58±1.02 hours which is comparable to 12-16 hours in other studies and with better induction to interval time. [12][13][14][15] Thus, vaginal dinoprostone gel with misoprostol is found to be an efficient and time saving drug for second trimester pregnancy termination. These drugs are easily available in any obstetric unit.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance to study by Tang et al 16 in which success rate was 91% for sublingual group and 95% for pervaginal group. Also Bhattacharjee et al 17 found success rate of 79% and 82% respectively in the sublingual and pervaginal groups and was statistically insignificant. Tanha et al 18 found the success rate of 61% in the pervaginal group and 70% in the sublingual group which was statistically insignificant.…”
Section: Discussionmentioning
confidence: 92%
“…This result corresponds with earlier study done by Tang et al 16 where in the sublingual group the interval was 13.2 hours and in the pervaginal group was 12 hours and the two values were also statistically insignificant. Bhattacharjee et al 17 found induction -abortion interval to be 14.1 and 14.5 hours in the sublingual and pervaginal groups respectively and was statistically insignificant.…”
Section: Discussionmentioning
confidence: 92%
“…In the same author study, sublingual misoprostol in gestational age <12 weeks reported success rate of about 86%. 9 Helena et al 11 demonstrated that repeated administration of 400 µg Misoprostol either vaginally or sublingually is an effective and acceptable option. However vaginal administration appears to produce better results among multiparous women, but more women had fever >38C in Vaginal route.…”
Section: Discussionmentioning
confidence: 99%